2020
DOI: 10.2196/16649
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Artificial Intelligence in Medical Care: Content Analysis of Social Media

Abstract: Background High-quality medical resources are in high demand worldwide, and the application of artificial intelligence (AI) in medical care may help alleviate the crisis related to this shortage. The development of the medical AI industry depends to a certain extent on whether industry experts have a comprehensive understanding of the public’s views on medical AI. Currently, the opinions of the general public on this matter remain unclear. Objective The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 41 publications
4
92
2
2
Order By: Relevance
“…All of our participants either strongly or somewhat supported AI development in healthcare, even if they felt suspicious of it. This does not align with previous research that demonstrates the mixed public perception of AI [ 8 , 19 ]. A 2020 study showcased that when talking about medical AI on social media, almost 40% of public posts were neutral or were against it [ 8 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…All of our participants either strongly or somewhat supported AI development in healthcare, even if they felt suspicious of it. This does not align with previous research that demonstrates the mixed public perception of AI [ 8 , 19 ]. A 2020 study showcased that when talking about medical AI on social media, almost 40% of public posts were neutral or were against it [ 8 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This does not align with previous research that demonstrates the mixed public perception of AI [ 8 , 19 ]. A 2020 study showcased that when talking about medical AI on social media, almost 40% of public posts were neutral or were against it [ 8 ]. Furthermore, a study conducted in 2019 describes that when given a short explanation of the development of AI, 41% of Americans somewhat support or strongly support the development of AI, and 22% of Americans somewhat or strongly oppose it [ 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study has limitations that need to be acknowledged. The number of participants we included was rather small, which limits generalization of our results to other populations; for example, a previous study suggested that Asian populations may anticipate a more disruptive development of medical AI with the potential replacement of health care professionals [35]. Apart from prior knowledge of AI, we did not observe other significant influences on its acceptance in the medical workflow, which might be attributed to the small sample.…”
Section: Discussionmentioning
confidence: 67%
“…As patients become more aware of AI and the increasing use of AI in healthcare, concerns around AI remain prevalent, with 43% of Europeans polling that AI was mostly harmful compared to 38% polling mostly helpful [ 98 ]. Lack of trust and human touch have been identified as drivers of negative perceptions [ 99 ], which could lead to patients becoming less open and thus impacting on clinicians’ ability to effectively treat them. With healthcare data breach and misuse frequency, magnitude, and resulting financial losses on the rise, largely due to increased incidents of hacking [ 100 ], a study unsurprisingly found that only 10.2% of patients would be willing to share their anonymous data with “a tech company, for the purposes of improving health care” [ 101 ].…”
Section: Discussionmentioning
confidence: 99%